(untitled) (Global Journal of Human-Social Science, 2024)
The introduction of the Enhanced Basic Education Act of 2013 has paved the way for the introduction of formal study of research in basic education across senior high school catering schools in the Philippines. Thus, it is imperative to assess how standards related to research in both learning, teaching, and leading standards are achieved by Science, Technology, Engineering, and Mathematics (STEM) providing schools and how these standards affect the quality of research papers produced by the students, and how to improve curricular structure and instruction based on the findings of the study. A total of 123 students, 16 teachers who took and taught research subjects last 2021-2022, and five school heads of two public schools participated in the study. Using four researcher-made instruments with good to excellent reliability results, in which teachers assessed learning standards, student and school heads measured teaching standards and teachers assessed leading standards.